An ideal feedstock, kusum (Schleichera triguga) for preparation of biodiesel: Optimization of parameters - Sharma Y.C.; Singh B. (My University, 2025)
Kusum (Schleichera triguga), a non-edible oil bearing plant has been used as an ideal feedstock for biodiesel development in the present study. Various physical and chemical parameters of the raw oil and the fatty acid methyl esters derived have been tested to confirm its suitability as a biodiesel fuel. The fatty acid component of the oil was tested by gas chromatography. The acid value of the oil was determined by titration and was found to 21.30 mg KOH/g which required two step transesterification. Acid value was brought down by esterification using sulfuric acid (H2SO4) as a catalyst. Thereafter, alkaline transesterification was carried out using potassium hydroxide (KOH) as catalyst for conversion of kusum oil to its methyl esters. Various parameters such as molar ratio, amount of catalyst and reaction time were optimized and a high yield (95%) of biodiesel was achieved. The high conversion of the feedstock into esters was confirmed by analysis of the product on gas chromatograph-mass spectrometer (GC-MS). Viscosity and acid value of the product biodiesel were determined and found to be within the limits of ASTM D 6751 specifications. Elemental analysis of biodiesel showed presence of carbon, hydrogen, oxygen and absence of nitrogen and sulfur after purification. Molar ratio of methanol to oil was optimized and found to be 10:1 for acid esterification, and 8:1 for alkaline transesterification. The amounts of H2SO4 and KOH, 1% (v/v) and 0.7% (w/w), respectively, were found to be optimum for the reactions. The time duration of 1 h for acid esterification followed by another 1 h for alkaline transesterification at 50 ± 0.5 °C was optimum for synthesis of biodiesel. © 2009 Elsevier Ltd. All rights reserved.